The importance of ancient Near Eastern literature in understanding ancient Arabic literature - شهرة, علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Ancient Arabic literature is still mysterious in some of its aspects, whether on the literary level of content, or on the linguistic level of language and style. There is no doubt that studying this literature within the framework of its sublime environment provides us with some solutions to the problem of understanding it on the two previous levels Looking at Arabic literature within the context of its limited Arab environment led to the emergence of deficient interpretations of some of its literary and linguistic material. Based on this, we call - through our research - for the necessity of paying attention to the Semitic languages ​​and knowing their literature, as they constitute an important source of our understanding of our ancient Arabic literature. Because the Arabs are one of the ancient Semitic peoples, and what is said about ancient Semitic life is true in many aspects of ancient Arab life as well.